Rekonstruksi Strategi Pembelajaran PAI Berbasis Penguatan Karakter dalam Meningkatkan Kedisiplinan dan Tanggungjawab Siswa di Era Digital - Darimus Darimus; Tyeva Agil Nadiansyah; Alif Akmal Al Irsyad; Nur Azizah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The development of digital technology has brought about significant changes in the world of education, including in the teaching of Islamic Religious Education. Although technology provides easier access to information, it also poses challenges in shaping students’ character, particularly in terms of discipline and academic responsibility. Therefore, a reconfiguration of learning strategies focused on character building is required to address these challenges. This study employed a qualitative descriptive approach and was conducted at a senior secondary school in Pekanbaru. Data were collected through observation, interviews and documentation, and analysed by sorting, presenting and drawing conclusions, with validity ensured through triangulation. Findings indicate that learning strategies combine conventional methods with digital media, but students’ discipline and academic responsibility still require improvement. Character building is implemented through habit formation, role modelling, and more active digital-based strategies. Supporting factors include school facilities and policies, whilst inhibiting factors involve low student awareness and the use of gadgets. This study concludes that the reconstruction of character-based learning strategies plays a crucial role in enhancing students’ discipline and academic responsibility in the digital age.